Postoperative delirium after partial laryngectomy in a middle-aged patient: A case report - Yu, Huiqian (Medicine (Baltimore), 2018)
RATIONAL: Postoperative delirium is a common occurrence in older patients. However, reports of postoperative delirium in middle-aged patients are limited, and the underlying mechanism of delirium in this patient population is not clear. PATIENT CONCERNS: A 45-year-old man who developed postoperative delirium on the second day after partial laryngectomy. Interviews of the surgical team, patient, and patient's spouse revealed that the patient was psychologically stressed, but had not been diagnosed or treated. The patient also suffered impairment in physiological functioning and sleep disturbance after surgery. DIAGNOSIS: Postoperative delirium. INTERVENTIONS: The postoperative delirium was treated with an antipsychotic drug. OUTCOMES: The patient recovered well. LESSONS: Preoperative psychological stress, which is often undiagnosed and untreated, can increase the risk of postoperative delirium in middle-aged patients undergoing laryngectomy. Therefore, screening for psychological stress and implementing strategies to prevent delirium should be considered for patients who undergo laryngectomy, even if they are not in high-risk older age groups.